Using Cognitive Academic Language Learning Approach (Calla) to Improve Students’ Speaking Ability - Umarsi, Nurhias; Usuluddin, Usuluddin; Nazri, M. Adib; Prasetyaningrum, Ary (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to test the effectiveness of the Cognitive Academic Language Learning Approach (CALLA) in teaching speaking. This research is a pre-experimental research with a pre-test and post-test design. This was carried out in the seventh grade at MTs TIA NW WANASABA in the 2023-2024 academic years. The sample consisted of 26 students. The research sampling used purposive sampling. The instrument speaks tests to collect data. Data were analyzed using Statistics 16.0 for win Statisticsdows. The results show that focus group discussions are effective for students with an average post-test score of 60.77 which is higher than the pre-test average score of 48.80. the hypothesis testing value of data analysis is 0.00, which is lower than 0.05. means that the alternative hypothesis of this research is accepted. Therefore, the Cognitive Academic Language Learning Approach (CALLA) is effective in teaching speaking ability. Considering the process and results of this research, the researcher suggests using the Cognitive Academic Language Learning Approach (CALLA) in teaching speaking.